2011
DOI: 10.1088/0029-5515/51/7/072001
|View full text |Cite
|
Sign up to set email alerts
|

Study on H-mode access at low density with lower hybrid current drive and lithium-wall coatings on the EAST superconducting tokamak

Abstract: The first high-confinement mode (H-mode) with type-III edge localized modes at an H factor of H IPB98(y,2) ∼ 1 has been obtained with about 1 MW lower hybrid wave power on the EAST superconducting tokamak. The first H-mode plasma appeared after wall conditioning by lithium (Li) evaporation before plasma breakdown and the real-time injection of fine Li powder into the plasma edge. The threshold power for H-mode access follows the international tokamak scaling even in the low density range and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 20 publications
10
108
1
Order By: Relevance
“…In addition, it is found that the power across the separatrix P loss increases with increasing neutral density while the power threshold P thr,08 is nearly unchanged with the similar initial plasma conditions (n e , B T , S), as indicated in figure 17(b). A reduced transition power threshold was observed with reduced edge neutral density, indicating that the edge neutral density near the X-point could be a key 'hidden variable' behind the H-mode access, which is consistent with previous experimental findings in EAST with the C wall [9]. Therefore, EAST experiments indicate that the low recycling regime with reduced edge neutral density enabled by lithium wall coating facilitates H-mode access, both for the C wall and Mo/C wall.…”
Section: Effects Of Lithium Wall Conditioning On P Thrsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, it is found that the power across the separatrix P loss increases with increasing neutral density while the power threshold P thr,08 is nearly unchanged with the similar initial plasma conditions (n e , B T , S), as indicated in figure 17(b). A reduced transition power threshold was observed with reduced edge neutral density, indicating that the edge neutral density near the X-point could be a key 'hidden variable' behind the H-mode access, which is consistent with previous experimental findings in EAST with the C wall [9]. Therefore, EAST experiments indicate that the low recycling regime with reduced edge neutral density enabled by lithium wall coating facilitates H-mode access, both for the C wall and Mo/C wall.…”
Section: Effects Of Lithium Wall Conditioning On P Thrsupporting
confidence: 91%
“…The I p keeps the same direction. Note that, unfortunately, we have made a mistake with the field direction in the 2010 campaign (reference [9], the third paragraph on p 2). Here we have double checked the direction of B T and can deduce the field direction through the E × B flow velocity with the toroidal and poloidal rotation direction measured by the magnetic coils.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments show strong dependence of the transition power threshold on the wall conditions and impurity concentration [33], however, the mechanism remains unclear.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, there is renewed interest in the L-H transition physics and power threshold [22][23][24][25][26][27][28][29][30][31][32][33], stimulated by the ITER requirement for H-mode operation in the initial non-active 5 phases with limited power available [3], as well as remarkable progress in high-resolution diagnostic capability at the plasma edge that allows us to gain deeper insights into the physics of the L-H transition [34]. Several powerful new diagnostics, such as multichannel Doppler Reflectometry [35][36][37][38], gas puff imaging (GPI) [39][40][41], beam emission spectroscopy (BES) [42,43], and reciprocating Langmuir probes [44][45][46], have recently been employed in several tokamaks [37][38][39][40][41][42][43][44][45] and a stellarator [35,36] to study the L-H transition physics near the threshold conditions, with some experimental results comparing favorably with the L-H transition model [15].…”
Section: Introduction and Brief Review Of The L-h Transition Studymentioning
confidence: 99%
“…This discharge, achieved with LHCD combined with other heating methods (ICRH, ECRH and NBI), has low and steady plasma radiation thanks to the lithium coating of the plasma facing components (PFC) and in particular of the divertor tungsten tiles. Lithium coverage reduces the effective charge Z eff of the plasma by trapping the oxygen atoms [7,8]. It also reduces the particle recycling leading to a change of the n e and T e profiles at the plasma edge, including the scrape-off layer [4].…”
Section: Introductionmentioning
confidence: 99%